An Analysis of Sasak Language Maintenance and Shift in Sumbawa: A Case Study at Surya Bhakti Neighbourhood in Sumbawa Regency - Ridwan Ridwan; Hizbul Wathoni; Hanofi Harianto; Selamet Riadi Jaelani (Educatio, 2022)
This research aimed to investigate the Sasak language maintenance and shift of Sasak people in Surya Bhakti neighborhood. This research was Qualitative descriptive method was employed in analyzing the data. There were 40 participants divided into young generation participants and old generation participants. There are 20 participants of the young generations that consist of 16 males and 4 females, while 20 participants of the old generation participants consist of 18 males and 2 females. Three techniques were employed to collect the data: observation, interview, and documentation. Observation and interviews serve as primary data sources. Meanwhile, documentation serves as the secondary one. The process of the interview was recorded. Meanwhile, a field note was used during the observation. Documents or documentation were used to complete the data findings from the observation and interview and take some pictures in the research area. Thus, all data from observation, interview, and documentation were analyzed. The research results show that Sasak people, both young and old generation participants, are proud of their language and cultural identity. The young generation participants maintain the Sasak language in Surya Bhakti neighborhood. In addition, the young generation participants have the proficiency in speaking Sasak language fluently and accurately than Sumbawanese. Furthermore, the data indicate that the old generations of Sasak people in Surya Bhakti neighborhood are more likely to use Sasak language than Sumbawanese when communicating daily with Sasak people in their community, even in their community outside of the neighborhood.